Selected issues in handwriting examination, graphology and their technology in document examination - Cieśla, Rafał; Grębowiec-Baffoni, Jolanta (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
This article aims at introducing the complex nature of handwriting examination for judicial purposes and the resulting competences which ahandwriting expert must have. The knowledge of neurophysiological conditioning of handwriting strokes, together with the knowledge of inks, their physical and chemical reactions with surfaces on which handwriting is applied, techniques allowing their observation and acquiring clear enlarged photographic images are indispensable for acorrect expert examination, explanation of how the conclusions were arrived at and illustrating the results. Appropriate selection of techniques of acquiring images requires not only the knowledge of optical and lighting equipment but also practical skills in its appropriate use. Thus, handwriting examination combines the knowledge from various areas: neurophysiology of movement, psychology of handwriting, chemistry, physics and use of optical equipment, which together guarantee objective and reliable examination yielding correct results.
Keywords: dokument; badanie pisma ręcznego; grafologia sądowa; badanie techniczne dokumentów; badanie biegłego; fałszerstwo; podpis; biegły